Commentary on a "unified approach to behaviours that challenge": getting it right? A family carer perspective. Issue 3 (13th November 2020) - Cooper, Vivien
Abstract : Purpose: The purpose of this paper is to provide an individual family-carer perspective on navigating the complex child, adult, education, health and social care systems focussing on what might be needed to get the right support in the right place at the right time for individuals with learning disabilities who display behaviour that challenges. Design/methodology/approach: This is a conceptual analysis, drawing on lived experience, policy and practice. Findings: Policy and best practice advocate a holistic, person-centred, outcome-focussed approach to supporting individuals with learning disabilities whose behaviour challenges, but the existing complex multiple organisational structures are not conducive to delivering this. Making the system work for people requires focussed leadership across all levels to co-ordinate and align the component parts. It is certainly possible to achieve, but it is currently unclear who will take responsibility for making this happen. Originality/value: Families are often the only constant in the lives of people with disabilities. This commentary highlights what is important to and for families when attempts are made to get the right support in the right place at the right time for individuals with learning disabilities who display behaviour that challenges.